Combined inhibition of IL1, CXCR1/2, and TGFβ signaling pathways modulates in-vivo resistance to anti-VEGF treatment. Issue 1 (January 2016) - Carbone, Carmine; Tamburrino, Anna; Piro, Geny; Boschi, Federico; Cataldo, Ivana; Zanotto, Marco; Mina, Maria M.; Zanini, Silvia; Sbarbati, Andrea; Scarpa, Aldo; Tortora, Giampaolo; Melisi, Davide
Abstract : Resistance of tumors to antiangiogenic therapies is becoming increasingly relevant. We recently identified interleukin-1 (IL1), CXC receptors (CXCR)1/2 ligands, and transforming growth factor β (TGFβ) among the proinflammatory factors that were expressed at higher levels in murine models resistant to the antivascular endothelial growth factor (anti-VEGF) antibody bevacizumab. Here, we hypothesized that the combined inhibition of these proinflammatory signaling pathways might reverse this anti-VEGF resistance. Bevacizumab-resistant FGBR pancreatic cancer cells were treated in vitro with bevacizumab, the recombinant human IL1 receptor antagonist anakinra, the monoclonal antibody against TGFβ receptor type II TR1, and a novel recombinant antibody binding CXCR1/2 ligands. The FGBR cells treated with these agents in combination had significantly higher levels of E-cadherin and lower levels of vimentin, IL6, phosphorylated p65, and SMAD2, and showed significantly lower migration rates than did their controls treated with the same agents without bevacizumab or with a single agent bevacizumab as a control. Consistently, the combination of these agents with bevacizumab reduced the FGBR tumor burden and significantly prolonged mice survival compared with bevacizumab in monotherapy. Tumors from mice receiving the combination treatment showed significantly lower expression of IL6 and phosphorylated SMAD2, higher expression of E-cadherin and lower levels of vimentin, and a significantly lower infiltration by CD11b + cells compared with bevacizumab-treated controls. This study suggests that inhibition of IL1, CXCR1/2, and TGFβ signaling pathways is a potential therapeutic approach to modulate the acquired resistance to anti-VEGF treatment by reversing epithelial–mesenchymal transition and inhibiting CD11b + proangiogenic myeloid cells' tumor infiltration. Abstract : Supplemental Digital Content is available in the text.